Implicit, Explicit, and Structural Barriers and Facilitators for Information and Communication Technology Access in Older Adults - Gomez-Hernandez, Miguel; Adrian, Stine Willum; Ferre, Xavier; Villalba-Mora, Elena (Frontiers in Psychology, 2022)
Spanish older adults’ usage of Information and Communication Technology (ICT) is challenged or facilitated by perception of usefulness, technology design, social identities (gender, social class, etc.), unspoken and political elements. However, studies on the use of ICT by older adults have traditionally focused on explicit-material interactions (usability studies, attitudes surveys, etc.). The article then analyzes how symbolic, institutional, and material elements enable or hinder Spanish older adults from using ICT. Our ethnographic methodology includes several techniques: 15 semi-structured interviews, participant observation in 9 ICT classes, online participant observation on WhatsApp and Jitsi during three months, and 9 phone-interviews due to COVID-19. The qualitative data was analyzed through Situational Analysis. The elements that hinder or facilitate ICT practice are implicit-symbolic (children’s surveillance, paternalism, fear, optimism, low self-esteem, and contradictory speech-act), explicit-material (affordances, physical limitations, and motivations), and structural-political (management, the pandemic, teaching, and media skepticism). Unprivileged identities hampered the ICT practices: female gender, blue-collar jobs, illiteracy, and elementary education. However, being motivated to use ICT prevailed over having unprivileged identities. Society and researchers should perceive older adults as operative with technologies and examine beyond explicit elements. We urge exploration of how older adults’ complex social identities and how situatedness affect ICT practice (e.g. institutions and symbols). Concerning explicit elements, the study encourages Spanish authorities to improve and adapt ICT facilities at public Senior Centers and older adults’ homes. ICT courses should foster tablet and smartphone training over computers.